Legal Protection for Suspects in the Investigation Process of Terrorism Criminal Acts in Order to Fulfill Human Rights n the Region of the Riau Islands Police - Raja Zailani; Dahlan Dahlan; Sayid Fadhil; Erniyanti Erniyanti; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The background of this study is the high number of terrorism cases in Indonesia that require strict law enforcement measures but must still respect human rights. Legal protection for suspects in the investigation process is crucial to ensure a fair legal process and in accordance with human rights standards regulated in various laws and regulations, including the Criminal Procedure Code, Law No. 5 of 2018, the 1945 Constitution, and Law No. 39 of 1999.The purpose of this study is to analyze the implementation of legal protection for suspects of terrorism crimes in the Riau Islands Police area, identify obstacles faced in implementing this protection, and formulate solutions to overcome these obstacles. The research method used is the empirical legal method, with a qualitative approach involving data collection through interviews, observations, and document studies.The results of the study indicate that the implementation of legal protection for suspects in the Riau Islands Police area is still less than optimal. The main obstacles identified include abuse of authority by law enforcement officers, lack of resources and capacity, and social stigma and discrimination against suspects. Abuse of authority often occurs in the form of unprocedural arrests and detentions, while limited resources result in a lack of adequate equipment and training for officers. Social stigma worsens the situation by hindering fair and humane legal protection. Based on the results of the study, it is recommended that supervision and accountability for the actions of law enforcement officers be strengthened, training and capacity building for officers be carried out continuously, and anti-stigma education and campaigns be carried out for the community. These steps are expected to increase the effectiveness of human rights protection for suspects, so that the process of investigating terrorism crimes can be carried out more fairly and in accordance with the principles of law and justice.